Membaca Simbol Dalam Teks Agama dengan Semiotika - Muhammad Taufik (UIN Sunan Kalijaga Yogyakarta, 2021)
The background of this study is based on the curiosity that the science of interpretation is considered by some people to be the only knowledge in understanding religious texts in this case the al-Qur'an. Whereas semiotics should be a tool that strengthens the existence of the science of interpretation. As a science, semiotics can be used as a tool of analysis or an approach to read symbols in religion. When observed, it appears that religion basically cannot be separated from talking about symbols, religion is in fact always related to symbols. The purpose of this paper is to reveal the extent to which semiotics plays a role in explaining the meaning of symbols contained in religion. Semiotics in this case is expected to provide a contribution which is expected to make it easier for us to understand how to read symbols in religion. The symbol in religion, in this case Islam, is mentioned in the Koran, which inevitably must have the right method of understanding it in order to get the real meaning, it is in this position that semiotics shows its existence. The method that the authors use in writing in this study uses the analysis-interpretive. That is, the elaboration or explanation of the research broadly and thoroughly, has a role to find, tell, and reveal the meaning contained in the object under study in this study. The results of this study explain that semiotics as a method can play a role in explaining religious messages contained in the holy book, in this case the al-Qur'an, many of which are expressed in the form of symbolic language. The meaning of this symbol is what the semiotics tries to uncover.